Analysis of Knowledge and Attitudes of Surgical Room Staff in Providing Early Breastfeeding Initiation (IMD) at Efarina Hospital, Pematangsiantar - Purba, Yeni Trisna; Pasaribu, Enrika T; T, May Linda Kristina (PT Inovasi Pratama Internasional, 2024)
This study aims to analyze the knowledge and attitudes of surgical room staff in providing early breastfeeding initiation (IMD) at Efarina Hospital, Pematangsiantar. This type of research is cross-sectional, which is a research design by conducting observations at the same time. The study was conducted in the surgical room of Efarina Hospital, Pematangsiantar, North Sumatra in 2024. This study will be conducted in January-March 2024. The population in this study are nurses and midwives who are surgical room staff at Efarina Hospital, Pematangsiantar in 2024, which is 10 people. After conducting research on the description of knowledge and attitudes of Surgical Room Officers in providing early breastfeeding initiation (IMD) at Efarina Hospital Pematangsiantar in 2024 with 10 respondents, the following results were obtained: The majority had sufficient knowledge, namely 4 people (40%), while the minority had good knowledge, namely 3 people (30%) and less knowledge, namely 3 people (30%). The majority had an attitude of agreement, namely 7 people (70%), while the minority had an attitude of disagreement, namely 3 people (30%).